Spontaneous lumbo-sacral epidural hematoma presenting as Cauda Equina syndrome: a case report - Sarwar, Mohammad; Tripathy, Laxminarayan; Bhattacharyya, Kalyanbrata (International Journal of Research in Medical Sciences, 2021)
Spinal epidural hematoma (SEH) is a rare condition and it accounts for less than 1% of all spinal canal space occupying conditions. Spontaneous SEH most commonly occurs in the cervical and thoracic regions. They present with neck or back pain with radiculopathy and/ or myelopathy. Early surgical decompression is the recommended treatment in the presence of progressive neurological deficits. Spontaneous SEH (SSEH) presenting as Cauda Equina syndrome (CES) are rarely reported in the literature. We present a case of SSEH presenting late with CES. Due to delay in presentation and multiple co-morbidities, patient was treated conservatively.